2017
DOI: 10.1038/s41598-017-03710-z
|View full text |Cite
|
Sign up to set email alerts
|

HCF-1 encoded by baculovirus AcMNPV is required for productive nucleopolyhedrovirus infection of non-permissive Tn368 cells

Abstract: Baculovirus Autographa californica multiple nucleopolyhedrovirus (AcMNPV) replicates in both Spodoptera frugiperda Sf21 and Trichoplusia ni Tn368 cells, whereas AcMNPV defective in hcf-1 (host cell-factor 1) gene productively infects only Sf21 cells, indicating that HCF-1 is indispensable for the AcMNPV productive infection of Tn368 cells. Here, we demonstrated that HCF-1 protein transiently expressed in Tn368 cells promotes the DNA synthesis of Hyphantria cunea MNPV (HycuMNPV), Orygia pseudotsugata MNPV and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Such factors also include HRF-1 ( Thiem et al., 1996 ) and HCF-1 ( Tachibana et al., 2017 ), which enhance viral DNA replication and viral protein synthesis in certain cell lines. These studies focused on how viral factors influence the viral multiplication process in a host and revealed that the functionality of a single viral factor may not be able to ease the constraints for all nucleopolyhedroviruses (NPVs) in a nonpermissive host ( Tachibana et al., 2017 ). A permissive and nonpermissive host may exert different effects on a virus.…”
Section: Discussionmentioning
confidence: 99%
“…Such factors also include HRF-1 ( Thiem et al., 1996 ) and HCF-1 ( Tachibana et al., 2017 ), which enhance viral DNA replication and viral protein synthesis in certain cell lines. These studies focused on how viral factors influence the viral multiplication process in a host and revealed that the functionality of a single viral factor may not be able to ease the constraints for all nucleopolyhedroviruses (NPVs) in a nonpermissive host ( Tachibana et al., 2017 ). A permissive and nonpermissive host may exert different effects on a virus.…”
Section: Discussionmentioning
confidence: 99%
“…Two genes that encode HCF-1 and APSUP were described as the host range determination factors in baculoviruses [89, 90]. It has been demonstrated that the AcMNPV HCF-1 protein is an essential viral factor for the productive NPV infection of TN-368 cells [93, 94]. Recently, a novel anti-apoptotic protein, APSUP, was identified in LdMNPV [95]; moreover, it has been demonstrated that the full-length Ld-Apsup could work against the apoptosis of Ld652Y cells induced by exposure to actinomycin D and UV and could interact with Ld-Dronc to prevent cells from undergoing apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…A notable factor is host cell-specific factor-1 ( hcf-1 ), which is absent in the BmNPV genome [3]. Hcf-1 is required for productive AcMNPV infections in nonpermissive Tn368 cells [34,35]; HCF-1 is an early protein that localizes to the cell nucleus [36], and promotes the replication of recombinant BmNPV in nonpermissive Tn368 cells [37]. In addition, GP64 has been identified as an AcMNPV and BmNPV host range determinant [1] and AcMNPV GP64 mediates BmNPV replication in Sf9 cells [4], thus, further work is needed to improve BmNPV infections in nonpermissive cells.…”
Section: Discussionmentioning
confidence: 99%